2012
DOI: 10.1017/s0024282912000205
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the importance of rock chemistry for saxicolous lichen communities of the New Idria serpentinite mass, San Benito County, California, USA

Abstract: Although several lichen inventories exist for European ultramafic sites, only four surveys of serpentine lichens for North America have been published to date. Of those, only one has been conducted in California. We conducted a survey of saxicolous lichens from ultramafic rocks (including nephrite, partially serpentinized peridotite, and serpentinite) and non-ultramafic rocks (including silica-carbonate, shale, and sandstone) at the New Idria serpentinite mass, San Benito County, California. X-ray Fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…Unlike vascular plants (Kruckeberg 2002) or saxicolous lichens (Rajakaruna et al 2012), bryophyte species and assemblages do not appear strongly specialized on serpentine in our data (see also Lepp 2001). Serpentine substrates were mainly occupied by widespread epigaeic or epilithic species that are found on a variety of different non-acid bedrock types.…”
Section: Discussionsupporting
confidence: 42%
“…Unlike vascular plants (Kruckeberg 2002) or saxicolous lichens (Rajakaruna et al 2012), bryophyte species and assemblages do not appear strongly specialized on serpentine in our data (see also Lepp 2001). Serpentine substrates were mainly occupied by widespread epigaeic or epilithic species that are found on a variety of different non-acid bedrock types.…”
Section: Discussionsupporting
confidence: 42%
“…Such investigations will likely reveal species that are endemic to the substrate or show a high affinity to ultramafic soils, as shown for such research conducted in South Africa (Venter et al 2015) and California, USA (Rajakaruna et al 2012). …”
Section: Discussionmentioning
confidence: 91%
“…Calcium increased the most after the addition of BC to serpentine soil. Given that Ca is often considered to be the most limiting nutrient for plant growth in serpentine soil (O'Dell and Rajakaruna 2011; Rajakaruna et al 2012), this observed increase in response to BC application is worthy of note. The available amounts of K, Ca, and Mg in the 5 % BC amendment were multiplied by 1.2-2.0-fold compared to the BC-unamended soil.…”
Section: Influence Of Biochar Amendments On Changes In Soil Ph Ec Tmentioning
confidence: 88%